Implementation of Fuzzy Based Simulation for Clone Detection in Wireless Sensor Networks - Manjunatha R C; Rekha K R; Nataraj K R (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Wireless sensor networks are usually left unattended and serve hostile environment, therefore can easily be compromised. With compromised nodes an attacker can conduct several inside and outside attacks. Node replication attack is one of them which can cause severe damage to wireless sensor network if left undetected. This paper presents fuzzy based simulation framework for detection and revocation of compromised nodes in wireless sensor network. Our proposed scheme uses PDR statistics and neighbor reports to determine the probability of a cluster being compromised. Nodes in compromised cluster are then revoked and software attestation is performed.Simulation is carried out on MATLAB 2010a and performance of proposed scheme is compared with conventional algorithms on the basis of communication and storage overhead. Simulation results show that proposed scheme require less communication and storage overhead than conventional algorithms.